Accurate stochastic initial and final failure of laminated plates subjected to hygro-thermo-mechanical loadings using Puck's failure criteria. (August 2016) - Gadade, Appaso M.; Lal, Achchhe; Singh, B.N.
Abstract: The second order statistics of first-ply and last-ply failure (FPF and LPF) response of laminated composite plate with random input parameters such as constituent material properties, plate thickness, volume fiber fraction and temperature difference, subjected to hygro-thermo-mechanical loading are investigated in this paper. Stochastic finite element method (SFEM) based on higher order shear deformation theory (HSDT) with material non-linearity via second order perturbation technique (SOPT) is formulated for computing mean and coefficient of variation (COV) of FPF and LPF using Puck's failure criteria. Failure strength of each ply and corresponding failure mode is predicted by using micromechanics based modeling approach. The effect of different environmental conditions, volume fiber fraction, lamination schemes, lamination angle, side to thickness ratio, different bi-axial loading on FPF and LPF response is investigated. The capability of the present SFEM in predicting FPF and LPF load statistics has been studied, by comparing the results obtained with the independent Monte Carlo simulation (MCS) technique. The predicted hygro-thermo-mechanical strengths of the several laminates are compared with the available experimental data and it shows good agreement. Highlights: Laminated composite plate subjected to hygro-thermo-mechanical loading is examined. Mean and standard deviation of initial and final failure is evaluated using second order perturbation technique and Monte Carlo simulation. The effect of fibre volume fraction and lamination angle are most affected on mean. Cross ply plate shows more strength under biaxial loading and different environmental conditions. The random change in Young's modulus of fibres and lamination angle are highly dominant.